Evaluation of complication rates after breast surgery using acellular dermal matrix: median follow-up of three years - Paprottka, Felix Julian; Schlett, Christopher L. (Plastic surgery international, 2017)
Introduction. Acellular dermal matrices (ADMs) are now commonly used for breast reconstruction surgery. There are various products available: ADMs derived from human (HADM), porcine (PADM), or bovine (BADM) sources. Detailed long-term follow-up studies are necessary to detect differences in complication rates between these products. Material and Methods. From 2010 to 2015, forty-one patients underwent 52 ADM-breast reconstructions in our clinic, including oncologic breast reconstructions and breast augmentation revisions (). 15x HADMs (Epiflex®/DIZG), 21x PADMs (Strattice®/LifeCell), and 16x BADMs (Tutomesh®/RTI Surgical) were implanted. Retrospective data collection with median follow-up of 36 months (range: 12-54 months) was performed. Results. Overall complication rate was 17% after ADM implantation (HADM: 7%; PADM: 14%; BADM: 31%). In a composite endpoint of complications and Red Breast Syndrome, a lower event probability was observed between BADMs, PADMs, and HADMs (44%, 19%, and 7%, resp.; for the trend). Furthermore, capsular contracture occurred in 6%, more frequently as compared to the current literature. Conclusions. When ADM-based reconstruction is indicated, the authors suggest primarily the use of HADMs and secondary the use of PADMs. It is shown that BADMs have the highest complication probability within our patient cohort; nevertheless, BADMs convey physical advantages in terms of flexibility and better aesthetic outcomes. The indication for the use of ADMs should be filled for each case individually.
Gesehen am 07.06.2018